A comprehensive evaluation on industrial & urban symbiosis by combining MFA, carbon footprint and emergy methods—Case of Kawasaki, Japan. (February 2017) - Ohnishi, Satoshi; Dong, Huijuan; Geng, Yong; Fujii, Minoru; Fujita, Tsuyoshi
Highlights: A comprehensive framework to analyze an industrial and urban symbiosis. Combination of material flow analysis, carbon footprint and emergy. A step-by-step process to develop database of comprehensive analysis. Policy implication for low carbon and resource independent urban development. Abstract: One proposed strategy to solve current environmental challenges is industrial and urban symbiosis (I/UrS); however, appropriate evaluation methods are needed so that the potential benefits of I/UrS can be quantified. Several evaluation methods have been applied separately to study I/UrS, but no integrated studies have been conducted by applying different methods in the same case study area. Therefore, this study aimed to establish a comprehensive framework to evaluate I/UrS by combining the material flow analysis (MFA), carbon footprint (CF) and emergy methods. First, we developed a unified database and step-by-step process to clarify the waste distribution and recycling processes in an industrial city. Then a baseline scenario and an I/UrS scenario were set up to define the baselines and effects of I/UrS and compare the results. Finally, the three methods were applied to identify physical features in the I/UrS system. The MFA-based results showed that the use of I/UrS led to a 6.4% reduction in the physical value of material use. The CF-based results indicated that reduction of waste and by-products results in a 13.8% reduction in CO2 e emissions. The emergy-based results showed that, with the implementation of I/UrS, the value of the emergy sustainability index (excluding labor and services) improved greatly (a 49.2% emergy reduction) as compared with the baseline case (a 14.3% reduction). In addition, the effects of implementing I/UrS by waste and by-product exchanges for blast furnace slag, scrap steel, waste paper, and waste plastic were evaluated. Whereas the CF reductions of unit ton of blast furnace slag is relatively low, emergy reductions of that is comparatively high. If policymakers only consider CF results when addressing the issue of climate change, the effects on emergy will be underestimated in this case. We conclude that the main actors in this area release huge emissions, but they also have a high potential to reduce their environmental loads. In addition, with appropriate designs, waste paper and plastics recycling could be highly efficient. Finally, the integration of the three evaluation methods should contribute to creating a low carbon and more resource independent society.